Disentangling the effects of multidimensional monetary policy on inflation and inflation expectations in the euro area - Catalina Martínez-Hernández (Freie Universität Berlin, School of Business & Economics, 2020)
The European Central Bank (ECB) has adopted a mixture of conventional and unconventional tools in order to achieve its mandate of price stability in the current low-inflation, low-interest-rate scenario. This paper contributes to the existing literature by providing a taxonomy of the ECB's policy toolkit and by evaluating its implications on price stability and the anchoring of inflation expectations. I carry out my analysis based on a high-frequency identification and the estimation of a large Bayesian Vector Autoregression. I find evidence of re-anchored expectations as response to quantitative easing and forward guidance, i.e. forecasters revise their long-run expectations upwards. Consequently, inflation increases, which stresses the crucial role of expectations for the transmission of monetary policy.
urn:nbn:de:kobv:188-refubium-28745-1
Keywords: E52; C55; C11; C32; E31; 330; Inflation Expectations; Monetary Policy; Large BVAR; High-frequency identification